ACOMPANHAMENTO DO CRESCIMENTO DE 04 ESPÉCIES ARBÓREAS PLANTADAS EM UMA NASCENTE EM RECUPERAÇÃO NO MUNICÍPIO DE MUNDO NOVO – MS - GONÇALVES, Cassiana de Aquino; CASTILHO, Selene Cristina de Pierri; SILVA, Thaís Tagliati; ROSSET, Jean Sérgio; MARRA, Leandro Marciano (ANAIS DO ENIC, 2018)
-